2018
DOI: 10.1038/s41388-018-0288-y
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoints PVR and PVRL2 are prognostic markers in AML and their blockade represents a new therapeutic option

Abstract: Immune checkpoints are promising targets in cancer therapy. Recently, poliovirus receptor (PVR) and poliovirus receptor-related 2 (PVRL2) have been identified as novel immune checkpoints. In this investigation we show that acute myeloid leukemia (AML) cell lines and AML patient samples highly express the T-cell immunoreceptor with Ig and ITIM domains (TIGIT) ligands PVR and PVRL2. Using two independent patient cohorts, we could demonstrate that high PVR and PVRL2 expression correlates with poor outcome in AML.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 46 publications
3
69
0
Order By: Relevance
“…Consistent with these findings, in vitro antibody-mediated blockade of PVR on acute myeloid leukemia cells was recently shown to increase the anti-leukemic effects of immune cells. 184 Similar findings were observed when melanoma cell lines were treated with anti-PVR antibody, leading to increased production of IFNγ by antigen-specific CTLs. 55 In addition, the first study using an anti-PVR mAb in in vivo tumor model also reported the anti-tumor properties of this treatment, with the Ab-inhibiting cancer metastasis.…”
Section: Anti-pvr Antibodies In Anti-tumor Therapysupporting
confidence: 60%
See 1 more Smart Citation
“…Consistent with these findings, in vitro antibody-mediated blockade of PVR on acute myeloid leukemia cells was recently shown to increase the anti-leukemic effects of immune cells. 184 Similar findings were observed when melanoma cell lines were treated with anti-PVR antibody, leading to increased production of IFNγ by antigen-specific CTLs. 55 In addition, the first study using an anti-PVR mAb in in vivo tumor model also reported the anti-tumor properties of this treatment, with the Ab-inhibiting cancer metastasis.…”
Section: Anti-pvr Antibodies In Anti-tumor Therapysupporting
confidence: 60%
“…185 According to another recent study, NSG mice that were reconstituted with human T cells and engrafted with tumor cells lacking both PVR and Nectin-2 exhibit prolonged survival compared to mice engrafted with WT (ligand expressing) tumor cells. 184 Although the indicated studies attributed the observed anti-tumor effects to immune cells, i.e., to the immune cell-dependent role of PVR, strategies targeting PVR might also rely on additional mechanisms. For example, given the role of PVR in cellular proliferation and its association with growth factor receptors, 34,35 researchers have hypothesized that the disruption of these complexes with antibodies might exert an anti-tumor effect.…”
Section: Anti-pvr Antibodies In Anti-tumor Therapymentioning
confidence: 99%
“…Expression of PVR in the AML cell line MV4-11 was used as a reference and set to 100%. 32 In the PVR-specific Western blot of the breast cancer samples, we detected a band of varying intensity with a mean expression level after densitometry of 23.6% and a range from 0% to 128.4% (Figure 2(a)). A positive correlation between PVR mRNA level and protein expression was found, with a Spearman correlation coefficient of 0.488 (p = .006) for probeset 32699_s_at.…”
Section: Pvr Mrna Levels Correlate With Protein Levels In Breast Cancmentioning
confidence: 93%
“…The protein lysate from the cell line MV4-11 was used as a reference and internal control in all blots. 18 After electrophoresis and blotting to PVDF membranes, PVR was detected using the monoclonal anti-PVR antibody L95. 63 Equal loading was verified by immunoblotting with anti-β-actin antibody (sc-47778, Santa Cruz Biotechnology).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation